Dynamic changes of hematological and hemostatic parameters in COVID-19 hospitalized patients: Potential role as severity biomarkers for the Chilean population: hematological and hemostatic parameters in COVID-19 - Letelier, Pablo; Delgado, Hugo; Garrido, Felipe; Quiñones, Francisco; San Martín, Andres; Hernández, Loreto; Garcés, Paola; Guzmán Oyarzo, Dina; Boguen, Rodrigo; Hernández, Alfonso; Medina, Gustavo; Schwerter, Patricia; et al. (Journal of Medical Biochemistry, 2024)
Background: COVID-19 is still a global health issue, there is limited evidence in South America regarding laboratory biomarkers associated with severe disease. The objective of our study was to identify hematological and hemostatic changes associated with severe COVID-19. Methods: A total of 170 hospitalized patients with COVID-19 were included in the study, defining their severity according to established criteria. Demographic, clinical, and laboratory (days 1, 3, 7, 15) data were obtained. We performed a statistical analysis, assuming significance with a value of p < 0.05. We analyzed the correlation between severity and biomarkers and established cut-off values for severe patients through ROC curves, estimating Odds Ratio associated with severe disease. Results: Day 1 was observed significant differences between moderate vs severe patients for leukocytes (WBC), Neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) and D-dimer, establishing cut-off points for each of them. The markers we found associated to risk of severe disease were WBC (OR=3.2396; p = 0.0003), NLR (OR=5.7084; p < 0.0001), PLR (OR=4.4094; p < 0.0001), Neutrophil (OR=4.1193; p < 0.0001), D-dimer (OR=2.7827; p = 0.0124). Conclusion: The results allow to establish basic laboratory biomarkers associated to severe disease, which could be used as prognostic markers.